(3NeQI CdMGf hQbI GdCdMGf aj TQM QSGdI GdTjN CQSdGfs - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj,J (B1143 (3g` s; (3GdTjN QSdGf , CQSdGf Hf jYbhH Hf YHO Gddg Hf YHO GdQMef GdLYHQj,J (B699 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd GdTjN YHOGdZfj GdfGHdSj hVYJg ddQSGdI GdTQjaI Hd GdLhgQI GdefjaI GdJi bPa HgG GdajV s
(3BNQgG (B:s
(3hbhdj HGdJGQjN ZRdGf adaX ZRdGf HGdMSGH JGQjN GdSfI hGdMeO ddg QH GdYGdejf Bejf s
(3GdfSNI HgG MhGTs
(3QSGdI GdTjN QSdGf GfXQ cTa GdXfhf L (B1 (3U`(B844s
(3Ydjg Jedc ai Chdgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B288 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B224s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs